The service mesh resilient service-to-service communication for cloud native applications - Miranda, George (O'Reilly Media, 2018)
There has been a recent surge in service mesh technology, with several open source options now available or in the works. For companies looking to build cloud-native applications, this dedicated infrastructure layer makes the flow of requests among microservices reliable, safe, and visible. In this ebook, George Miranda from Bouyant examines the problems that service mesh technology solves and provides pragmatic guidance for introducing it into your infrastructure. In cloud-native architectures, your network becomes the fundamental determining factor for how your applications behave at runtime. The shift to microservices solves many problems, but it also introduces a new set of reliability, performance, and security challenges inherent to managing distributed systems. A service mesh helps you wrangle that complexity by providing a uniform way to manage, monitor, and control your production applications. This ebook shows you how. Examine how the service mesh injects previously missing observability into microservice communications Use service mesh primitives to improve your application's resiliency Learn how implementing a service mesh can help secure your services Explore real use cases that demonstrate how several companies solved problems by using a service mesh Get a set of practical questions that will help you navigate the service mesh ecosystem.
Online resource; title from cover (Safari, viewed September 7, 2018)
Keywords: Cloud computing; Computer architecture; Computer networks -- Management; Infonuagique; Ordinateurs; Architecture; Réseaux d'ordinateurs; Gestion; Computer networks; Management